Solidaritas Bagi Pasifik Selatan: Analisis Kebijakan Luar Negeri Selandia Baru dalam Menanggapi Isu Perubahan Iklim pada masa Pemerintahan Jacinda Ardern - Lyra Asaria Uthan; Mohamad Rosyidin; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Since Jacinda Ardern's period as a prime minister in New Zealand, the country has contrasted climate change policy with the previous prime minister. Ardern's concern about climate change leads New Zealand to change the countries' diplomatic relations and add its foreign aid to the Pacific Islands countries. New Zealand's orientation and concern for the regional climate change crisis show a shift in Jacinda Ardern's leadership with her predecessor. This research aims to answer the research question: